Priority quality traits for gendered sweetpotato breeding in Mozambique - Mayanja, S.; Tinyiro, S.E.; Ogwal, D.M.; Makunde, G.S.; Naico, A.; Nakitto, M.; Ssali, R.T.; Andrade, M.I. (Frontiers Media, 2023)
Introduction: Sweetpotato breeders strive to develop varieties that address productivity challenges farmers face in sub-Saharan Africa (SSA). However, adoption of these varieties is low, partly attributed to limited attention to attributes desired by the end-users.